Trajetos e conexões: vereadoras negras eleitas em 2020 na cidade de São Paulo e a prática política nas redes sociais - Guedes, Aline Santos de Campos (2021)
This research analyses the relation between personal trajectory of black women and politics trajectory which provided the arrival of São Paulo City Council as councilors elected in 2020. Starting from the historical perspective from the politic access and of hardened communication for these women by the racist social structure, male chauvinist, classy and LGBTphobic and the path of the black women movement, intends to investigate the influencing factors in feminists acting and their struggle, also identify which impediments exist and how they establish in activist practices. Based in Afro-Latin American theorical contributions to the gender, race and class debate, the concepts studied in the biographies were related to the black women political actions with the councilors’ deep interviews. Thereby, propose to analyze their actions, articulating the “street-network” flow, and beholding the rescue of base concepts to sociopolitical transformations considering social networks as a tool of political mobilization